2022
DOI: 10.1021/acsapm.2c01095
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Thermoresponsive Ultrafiltration Membranes from Polymerization of Lyotropic Liquid Crystals

Abstract: In this study, we present the fabrication of a two-step thermoresponsive ultrafiltration (UF) membrane through polymerization of a lyotropic liquid crystal (LLC). A mixture of commercially available Pluronic F127 block copolymer, water (containing ammonium persulfate as the initiator), and polymerizable oil (n-butyl acrylate/ethylene glycol dimethacrylate) is used to create an LLC with a lamellar structure, as characterized by cross-polarized light microscopy and atomic force microscopy. Differential scanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Leveraging the extensive surface area of clothing textiles, they can be transformed into smart interfaces, offering benefits in managing temperature and moisture for the wearer [47], providing active thermoregulation [48]. Other example are filtration membranes, where temperature-sensitive materials can optimize the filtration efficiency by adjusting pore size in response to temperature changes [49]. Furthermore, in biomedical applications, fibrous structures designed to respond to temperature fluctuation can be used in drug delivery systems [50].…”
Section: Temperaturementioning
confidence: 99%
See 3 more Smart Citations
“…Leveraging the extensive surface area of clothing textiles, they can be transformed into smart interfaces, offering benefits in managing temperature and moisture for the wearer [47], providing active thermoregulation [48]. Other example are filtration membranes, where temperature-sensitive materials can optimize the filtration efficiency by adjusting pore size in response to temperature changes [49]. Furthermore, in biomedical applications, fibrous structures designed to respond to temperature fluctuation can be used in drug delivery systems [50].…”
Section: Temperaturementioning
confidence: 99%
“…This brought about a further increase in the molecular weight cutoff to 570 kDa (pore size ~50 nm). These temperature-induced alterations contributed to increased membrane porosity, leading to improved hydration capacity, enhanced permeability, and improved cleaning efficiency, particularly in dealing with fouled membranes [49].…”
Section: Thermo-responsive Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…The incorporation of stimuli-responsiveness into membranes can offer new opportunities for applications by enabling dynamic selectivity and permeability, and enhanced cleaning of a fouled membrane. ,, While there are some reports on the production of stimuli-responsive ultrafiltration (UF) membranes by using LLC templates, , there are only a few studies in the literature available on the synthesis of stimuli-responsive NF membranes from LLC templates. Zhu et al reported an LLC-based sodium selective isoporous membrane, which offered ion conductive channels lined with carboxylate groups.…”
Section: Introductionmentioning
confidence: 99%